Pengembangan Ensiklopedia Digital Teknologi Listrik Berbasis Contextual Teaching and Learning (CTL) - Jules Nurhatmi; Muhammad Rusdi; Kamid Kamid (Universitas Jambi, 2015)
Digital Encyclopedia of Electrical Technology Development has 5 goals, namely the development of the recommended procedure, determine the development requirements, the recommended procedure to use, knowing the terms of use that can improve the success of the use of, and determine the impact of the use of Digital Encyclopedia of Electrical Technology-Based Contextual Teaching and Learning (CTL ) that can provide contextual knowledge to the students about electricity as a source of learning physics junior level. Development model adopted in this study ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) and 5 apply the constructivism learning component CTL, find, ask, modeling, and reflection. Product trials carried out in two phases, namely a small test group and large group trials. Small group trial to assess the practicalities, applicability, and ease. Large group trial to assess the practicalities and impact of the use.